The interplay between class heterogeneity and teaching quality in primary school. (2017) - Decristan, Jasmin; Fauth, Benjamin; Kunter, Mareike; Büttner, Gerhard; Klieme, Eckhard
Highlights: Dealing with students' different abilities in class is a topic of major interest. Research provides little evidence of the benefits of ability grouping. The results indicate a positive interplay between heterogeneity and teaching quality. Students in heterogeneous classes particularly benefitted from teaching quality. Abstract: Dealing with students of different abilities in class is a topic of major importance in educational research and practice. While a number of strategies have been implemented to reduce class heterogeneity, there is little empirical evidence of their benefits. Rather, classroom processes are assumed to play a vital role in the effect of heterogeneity on students' achievement. In this longitudinal study of 54 primary school classes, we examine the interplay between class heterogeneity and teaching quality and its effect on students' conceptual understanding. Results of multi-level regression analyses revealed no effect of heterogeneity on student outcomes. Instead, the results indicated a positive interaction: Students in classes of heterogeneous ability particularly benefitted from cognitive activation and a supportive climate.